Penerapan dan Analisa Pengaruh Total Quality Manajement (TQM) terhadap Kepuasan Pelanggan pada “UD. Purnama Jati“ - Nada, Klarisa Qutrun; Vitriyah, Nurul Lailatul (KUBIS, 2024)
The purpose of this study was to determine the application of Total Quality Management (TQM) indicators to customer satisfaction at UD Purnama Jati and the effect of TQM variable indicators on customer satisfaction at UD Purnama Jati. These indicators consist of focus on customers, obsession with quality, teamwork and long-term commitment. This research includes research using qualitative and quantitative descriptive approaches. The population in this study are customers at UD Purnama Jati. The sampling technique used accidental sampling with coincidence-based determination and sample determination using purposive sampling with the criteria of buyers over the age of 18 years, the respondents in this research were 45 people. Data collection techniques used observation, interviews, questionnaires or documentary questionnaires. Data analysis uses multiple linear regression tests that have been teste for validity, reliability, autocorrelat on, heteroscedasticity The results of the study show that focus on customers, obsession with quality, teamwork have a partial effect on customer satisfaction. Meanwhile, long-term commitment has no partial effect on customer satisfaction. Meanwhile, long-term commitment has no partial effect on customer satisfaction. Simultaneously focus on the customer. Obsession with quality, teamwork, long-term commitment simultaneously influence customer satisfaction at UD Purnama Jati.